Pemberdayaan Perempuan dalam Pengembangan Desa Wisata Pekunden Kecamatan Banyumas Kabupaten Banyumas - Andhinie Fathimatul Hasanah; Zidan Arief Maulana; Sri Kencana Wulan; Sintia Nur Anggitasari (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This article analyzes women’s empowerment in the development of Pekunden Tourism Village, Banyumas District, Banyumas Regency, focusing on the role and contribution of women in tourism based on local creativity. Using Kartasasmita's (1996) empowerment framework, which includes enabling, empowering, and protection, the study collects data through interviews, observations, and documentation from key informants such as the village head, tourism awareness group, and women entrepreneurs in Oemah Batik, Oemah Manggleng, Dragon Fruit Garden, and Kampoeng Nopia Mino. The findings reveal that women’s empowerment in Pekunden Tourism Village has fostered a supportive environment, enhanced women’s capacity, and ensured business protection. Training programs and the development of local products have expanded economic opportunities, increased women’s participation in decision-making, and improved family welfare. Overall, women’s empowerment has made a significant contribution to local socioeconomic development, positioning Pekunden Tourism Village as a successful model of synergy between tourism and community empowerment. This case exemplifies the positive impact of regional autonomy in promoting local creativity and economic growth through tourism.